2020
DOI: 10.24815/ijdm.v3i2.17621
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Effectiveness and Inclusions: Public Perceptions on Indonesia’s Disaster Management Authorities

Abstract: Disaster risk events always have impacts on disaster losses in terms of the sustainability. The phenomena of natural hazards continue to threaten the social and economic livelihoods of the community, ─ while policies and stipulated regulations for mitigating disaster risks reduction (DRR) endlessly become polemics both in national and local government institutions. The study was conducted to address public perceptions on the effectiveness of Indonesia’s Disaster Management Authorities in managing DRR across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…The succession key to effective disaster risk reduction is adequate preparation prior to the disaster occurrence (Lesmana and Purborini, 2019). On the other hand, to achieve the proper functioning of these agencies, a command, monitor and control system is necessary in place and it should be synergized with the policies and other government institutions (Tanesab, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The succession key to effective disaster risk reduction is adequate preparation prior to the disaster occurrence (Lesmana and Purborini, 2019). On the other hand, to achieve the proper functioning of these agencies, a command, monitor and control system is necessary in place and it should be synergized with the policies and other government institutions (Tanesab, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study conducted by Tanesab (2020) revealed that the national and regional disaster management authorities in Indonesia are ineffective due to a lack of effective communication, coordination, collaboration and synchronization in disaster risk reduction. Other constraining factors, such as limited leadership capability in decision-making through vertical and horizontal negotiations and a lack of persuasive approaches to involve the community in all disaster management cycles were also stated.…”
Section: Introductionmentioning
confidence: 99%
“…This As far as the authors know, no comprehensive work is dedicated to government and local institutions in COVID-19 disaster communication. The role of universities in community empowerment in the COVID-19 era [7], government public communications published by national online media [8], disaster communication in earthquake mitigation [9], and public perceptions of Indonesia's disaster management authorities [10] are a few prior studies that the author considers relevant to this paper. The combination of cooperation between community institutions and governmental institutions in longterm catastrophe communication, specifically the COVID-19 pandemic, needs to be thoroughly covered in this research, though.…”
Section: Introductionmentioning
confidence: 99%
“…The framework provides a befitting conceptual underpinning for this study. These frameworks challenge the role of HEIs to the position of executing disaster management for SD through knowledge management, innovation, education and training, research, information exchange, dissemination and public awareness, national institutional frameworks and community participation (Tanesab 2020 ). The fundamental goal of the HFA is to challenge HEIs to consistently play a pivotal role in promoting SDG through the implementation of climate and disaster management curriculum, research projects and simulations.…”
Section: Introductionmentioning
confidence: 99%